Impairments and comorbidities in adults with cerebral palsy and spina bifida: a meta-analysis - Sattoe, Jane N. T.; Hilberink, Sander R. (Frontiers in Neurology, 2023)
Introduction Aging with a childhood-onset disability, such as cerebral palsy (CP), spina bifida (SB), and muscular diseases (MD), comes along with significant impairments and comorbidities. Despite the increasing evidence an overall picture is lacking. This study aimed to review the literature about adults with CP/SB/MD and impairments and comorbidities to perform a meta-analysis. Materials and methods Embase, PubMed, Cinahl, and Google Scholar were searched (2000–2020). Search terms included adults with one of the aforementioned disabilities combined with impairments and comorbidities. If specific impairments or comorbidities were reported by at least four studies, these were included in the study. Pooled prevalence (95% Confidence Interval) of impairments/comorbidities were calculated. Results The search yielded 7,054 studies of which 95 were included in the meta-analysis (64 CP, 31 SB, 0 MD). In total estimates were calculated for 26 (CP) and 11 (SB) outcomes. In adults with CP, pain [56.4% (95%CI 48.8–63.8)], deformities [44.2% (95%CI 12.9–78.4)], intellectual disability [37.2% (95%CI 26.7–48.3)], and fatigue [36.9% (95%CI 24.6–50.1)] were most prevalent; renal disease [3.0% (95%CI 2.1–4.2)] and stroke/rheumatic diseases {4.8% (95%CI 3.4–6.5; 4.8% (95%CI 1.5–9.9)] respectively} were least prevalent. For adults with SB, bladder incontinence [60.0% (95%CI 50.5–69.2)], bowel incontinence [49.2% (95%CI 34.5–64.0)], pain [44.1% (95%CI 27.4–61.5)], and sleeping problems [30.3% (95%CI 4.7–65.8)] were most prevalent; diabetes [4.8% (95%CI 2.8–7.3)] and renal disease [8.7% (95%CI 2.0–19.9)] were least prevalent. The included studies showed large heterogeneity. Conclusions More research is needed to study health issues in adults with MD. Adults with CP or SB deal with a variety of health issues. More attention for the mental health of these adults is needed. There also is a need for accessible and adequate screening, preventive measures and clinical follow-up.